Possible binary progenitors for the Type Ib supernova iPTF13bvn. Issue 3 (28th November 2014) - Eldridge, J. J.; Fraser, Morgan; Maund, Justyn R.; Smartt, Stephen J.
Abstract: Cao et al. reported a possible progenitor detection for the Type Ib supernovae iPTF13bvn for the first time. We find that the progenitor is in fact brighter than the magnitudes previously reported by approximately 0.7–0.2 mag with a larger error in the bluer filters. We compare our new magnitudes to our large set of binary evolution models and find that many binary models with initial masses in the range of 10–20 M⊙ match this new photometry and other constraints suggested from analysing the supernova. In addition, these lower mass stars retain more helium at the end of the model evolution indicating that they are likely to be observed as Type Ib supernovae rather than their more massive, Wolf–Rayet counter parts. We are able to rule out typical Wolf–Rayet models as the progenitor because their ejecta masses are too high and they do not fit the observed SED unless they have a massive companion which is the observed source at the supernova location. Therefore only late-time observations of the location will truly confirm if the progenitor was a helium giant and not a Wolf–Rayet star.